La Alianza del Pacífico y el CPTPP: ¿alternativas para la solución de diferencias ante la OMC? - Gallardo-Salazar, Natalia (2021)
The World Trade Organization (WTO) dispute settlement system is currently in crisis because the WTO Appellate Body ceased effectively functioning in December 2019. As a consequence, the WTO Dispute Settlement Body is unable to adopt a panel report if a party to the dispute notifies its intention to appeal. In this context, this article analyzes what factors may influence the complaining parties’ decision on whether to recur to two regional trade agreements (RTA), namely the Pacific Alliance and the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), as alternative fora to WTO dispute settlement. After a comparative analysis of dispute settlement rules in both RTAs and the WTO Dispute Settlement Understanding, we conclude that procedural and institutional factors will arguably be relevant for complaining parties that wish to select a dispute settlement forum.